Association of CDKN2A/B deletions with survival of patients with diffuse large B-cell lymphoma - M. V. Sarpova; E. V. Tregubova; D. A. Diakonov; E. V. Vaneeva; V. A. Rosin; S. V. Samarina; E. L. Nazarova (Бюллетень сибирской медицины)
Aim. To define the association of CDKN2A/B deletions in the 9p21 locus with survival of patients with diffuse large B-cell lymphoma.Materials and methods. The study included 105 patients with diffuse large B-cell lymphoma who received firstline therapy with R-CHOP. A deletion of 9p21 was detected by fluorescent in situ hybridization of tumor tissue biopsy samples. Deletions of CDKN2A and CDKN2B were determined by real-time quantitative polymerase chain reaction. The overall survival and the progression-free survival were calculated by the Kaplan – Meier method with plotting of survival curves (the log-rank test). The risk of event occurrence was determined by the Cox regression analysis with the calculation of the risk ratio (RR) and 95% confidence interval (CI). The differences between the variables were considered statistically significant at p < 0.05.Results. The deletion of the chromosomal region 9p21 was detected in the biopsy samples in 16.2% of patients. The CDKN2A deletions were detected in 23.8% of patients and CDKN2B loss – in 28.6% of patients. The progressionfree survival was significantly lower in patients with the 9p21 deletion than in those without this aberration: 29.4% vs. 62.5%, respectively (p = 0.012; RR = 2.26; 95% CI = 1.17–4.38). The risk of disease progression at low and low-intermediate values of the International Prognostic Index was 5.9 times higher in patients with the CDKN2B deletion than in patients without this abnormality.Conclusion. Deletion of the chromosomal region 9p21 is associated with low progression-free survival in patients with diffuse large B-cell lymphoma. Loss of CDKN2B is associated with a high risk of disease progression in patients with low and low-intermediate risk according to the International Prognostic Index.